2023
DOI: 10.1093/ofid/ofac584
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Outpatient Antibiotic Prescribing for Acute Respiratory Tract Infections in a Commercially Insured Population, United States, 2017

Abstract: Background Studies have shown that the Southern United States has higher rates of outpatient antibiotic prescribing rates compared with other regions in the country, but the reasons for this variation are unclear. We aimed to determine whether the regional variability in outpatient antibiotic prescribing for respiratory diagnoses can be explained by differences in prescriber clinical factors found in a commercially insured population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This finding supports previous observations of high AMR prevalence in US southern-border regions, which may be influenced by access to antimicrobials, and their overuse, without a prescription in Mexican pharmacies along the US-Mexico border [ 21 ]. Studies have also demonstrated higher outpatient antibiotic prescribing, including inappropriate prescribing, in Southern US states versus other US regions [ 1 , 22 ], which might reflect regional differences in antibiotic stewardship [ 1 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports previous observations of high AMR prevalence in US southern-border regions, which may be influenced by access to antimicrobials, and their overuse, without a prescription in Mexican pharmacies along the US-Mexico border [ 21 ]. Studies have also demonstrated higher outpatient antibiotic prescribing, including inappropriate prescribing, in Southern US states versus other US regions [ 1 , 22 ], which might reflect regional differences in antibiotic stewardship [ 1 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, non-clinical factors such as demographic and socioeconomic differences [ 13 ], or differences in patient demand and prescription practices have been suggested to underlie regional variations [ 17 ], and the influence of patient demand on inappropriate antibiotic prescriptions is well documented [ 18 , 19 ]. Supporting small-area differences, calls have been made to take into account small-area regional factors in devising targeted interventions to support rational prescription practices [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among commercially insured patients in 2017 with an acute respiratory tract infection, those living in the South were 34% more likely than those in the West to receive an antibiotic [ 20 ]. Similarly, examination of medical records from the National Ambulatory Medical Care Survey from 2012 to 2013 revealed that patients in the East South Central region (i.e., AL, KT, MS, TN) were more likely than those in Pacific states (CA, OR, WA) to be diagnosed with a condition where an antibiotic would be prescribed [ 21 ]. Kentucky had the highest prescription rates (1281 prescriptions per 1000 persons), which was about four-fold higher than Alaska (348 per 1000 persons) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While regional and state-level disparities in antibiotic prescribing are well known [ 20 , 21 ], it is important to provide updated information to provide information on whether stewardship efforts have been successful in driving down these population-level differences. The low-income Medicaid population may face challenges that are different from those that are commercially insured.…”
Section: Introductionmentioning
confidence: 99%